AN Unusual case of osteoblastoma in an elderly female: A case report and a review - Dahiya, Ankita; Srinath N; Umashankar D N; Ashish Gupta; Mahadeepa Kar (Medico Research Chronicles, 2020)
Osteoblastomas are a rare entity encountered as benign osseous tumor with propensity of occurence towards the vertebral column and long bones. Commonly occurs in young middle aged  males with mandible as a site of predilection in facial skeleton. Differential diagnosis of osteoblastoma holds a challenge in attaining a final diagnosis. Osteoid osteoma, cementoblastoma, osteosarcoma, aggressive fibrous dysplasia, and ossifying fibroma share a similar clinical behavior, radiological and histological behavior. This article aims to report a case of osteoblastoma of an aggressive variety appearing in maxilla. It aims to gain a better understanding of clinical, histological, radiological and differential diagnosis of osteoblastoma. A review of English language literature 2006 revealed 43 previously reported cases of osteoblastoma appearing in maxilla and mandible since 1967. 16 cases including this one is added to the previous well documented review of literature by Jones where he included additional 24 cases to the previously reported 43 cases. Brief discussion and review on treatment modalities are analysed.